UNIAXIAL FILMS OF MAXIMALLY CONTROLLABLE RESPONSE UNDER VISIBLE LIGHT - Tulegenov, Dias; Valagiannopoulos, Constantinos (Nature Research, 2020)
The controllability of photonic setups is strongly related to how coherently their outputs react to changes in their inputs; such a generic concept is treated in the case of films comprising multilayers of tilted optical axes, under visible light. The optimized designs incorporate ordinary metals or semiconductors while being able to achieve practically all the combinations of reflected, transmitted and absorbed power within the passivity limits. Importantly, most of the proposed structures exhibit substantial robustness to manufacturing defects and are fabricable with various methods. Therefore, they can make indispensable pieces of integrated photonic systems by improving their light-controlling operation for applications ranging from steering and electrodynamic switching to filtering and optical signal processing.
Keywords: Research Subject Categories::NATURAL SCIENCES